IDENTIFIKASI KEKAYAAN JENIS TUMBUHAN PAKU DI SEKITAR ALIRAN SUNGAI DESA WAITATIRI MALUKU TENGAH - Sianturi, Advend Sri Rizki; Tuapattinaya, Prelly Marsell Jolanda (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2025)
Background: Pteridophytes are vascular plants that reproduce via spores rather than seeds.This research aims to identify the richness of fern species (Pteridophyta) in Waitatiri Village, Central Maluku, based on morphological characteristics and benefits. Methods: Data collection was carried out in December 2024 using the direct observation method by taking samples and analyzing the morphology of ferns in the river area of ​​Waitatiri Village. Results: The research results showed that there were 10 species of ferns belonging to 8 families and 8 genera, with the Selaginellaceae family being the most dominant throughout the course of the research. Several species such as Asplenium rhizophyllum and Asplenium nidus have significant ecological value and benefits, such as as a food source, traditional medicine and ornamental plant. Conclusion: This research emphasizes the importance of conservation and use of ferns as part of biodiversity with ecological, economic and aesthetic functions.